THE INFLUENCE OF THE 3-D MEDIA ON INDONESIAN LEARNING OUTCOMES OF GRADE II ELEMENTARY SCHOOL STUDENTS - Asmaliyatus Sholichah; Haris Supratno; M. Bambang Edi Siswanto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The purpose of this study is to determine the effect of the use of 3-D learning media towards the student’s Indonesian learning result of 2nd grade students in SDI Sabilillah on the sketch material. The type of research used was Quasi Experiment. The subjects of the study were 2nd grade students in SDI Sabilillah in year 2019/2020 which were divided into experimental class and control class. The results of the pretest and posttest tests conducted were obtained an average pretest result of 49.5 and an average posttest of 70.25 in the control class, and the average results of the pretest 50 and an average posttest of 80.25 in the experimental class. After the t test was performed on the pretest and posttest in the control class to get the results of thitung> ttable or 3.67> 2.093 then Ho was rejected and Ha was accepted, so it could be concluded that there was a positive influence on the control class. T test results in the experimental class were thitung> ttable or 3.73> 2.093 then Ho was rejected and Ha was accepted, so it could be concluded that there was a positive influence on Indonesian language learning by using 3-D media. When it was compared to the t test in the experimental class and the control class, namely (3.73)> (3.67) it could be seen that there was a difference between the experimental class using 3-D learning media and the control class using conventional learning, and the influence of using 3-D media were greater than conventional learning.